2020
DOI: 10.15252/embj.2019102808
|View full text |Cite
|
Sign up to set email alerts
|

HNF1A recruits KDM6A to activate differentiated acinar cell programs that suppress pancreatic cancer

Abstract: Defects in transcriptional regulators of pancreatic exocrine differentiation have been implicated in pancreatic tumorigenesis, but the molecular mechanisms are poorly understood. The locus encoding the transcription factor HNF1A harbors susceptibility variants for pancreatic ductal adenocarcinoma (PDAC), while KDM6A, encoding Lysinespecific demethylase 6A, carries somatic mutations in PDAC. Here, we show that pancreas-specific Hnf1a null mutant transcriptomes phenocopy those of Kdm6a mutations, and both defect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 87 publications
(128 reference statements)
2
39
0
Order By: Relevance
“…HNF1A is a homeodomain transcription factor that had been thought to be a pancreatic tumor suppressor. It was also shown that HNF1A loss partially phenocopies KDM6A KO in Kras G12Dinduced pancreatic cancer (20). KDM6A also plays a role in suppressing myeloid leukemogenesis independently of its demethylase activity.…”
Section: Kdm6a Mutations In Developmental Diseases and Cancermentioning
confidence: 95%
See 2 more Smart Citations
“…HNF1A is a homeodomain transcription factor that had been thought to be a pancreatic tumor suppressor. It was also shown that HNF1A loss partially phenocopies KDM6A KO in Kras G12Dinduced pancreatic cancer (20). KDM6A also plays a role in suppressing myeloid leukemogenesis independently of its demethylase activity.…”
Section: Kdm6a Mutations In Developmental Diseases and Cancermentioning
confidence: 95%
“…The mechanism behind KDM6A genomic targeting also requires further investigation. It has been hinted that certain TFs could interact with KDM6A, which, in turn, recruits MLL3/4 to activate enhancers (20,24).…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…HNF1A is a transcription factor that regulates the differentiation of endodermal genes and regulates the acinar cell identity. Aberrant expression of HNF1A alters lineage differentiation, growth, and the acinar cell plasticity via binding at the enhancers of several acinar genes [48]. HNF1A has been linked to tumor suppressive role based on tumor expression [49,50] but has been recently identified to promote cancer stemness [16] and resistance to paclitaxel and tyrosine kinase inhibitors [10] in pancreatic tumorigenesis.…”
Section: Aatk Expression In Vivo Associates With Nuclear Vav1 Localizmentioning
confidence: 99%
“…6 The basal-like subtype is characterised by activation of the MYC pathway together with pro-inflammatory pathways, hypoxia networks, metabolic reprogramming, autophagy, epidermal growth factor and transforming growth factor-β (TGF-β) signalling and activation of the ΔNp63 pathway, 3 as well as being enriched in mutations in the tumour-suppressor TP53 and the lysine demethylase KDM6A and showing silencing of endodermal identity transcription factors, such as GATA6 or hepatocyte nuclear factor family members. 3,[6][7][8][9][10][11] The clear differences in the molecular underpinnings of the PDAC subtypes illustrate that understanding the biological mechanisms that drive these subtypes and connect the different subtypes with novel therapies represents one promising approach to improve the outcome of the disease.…”
Section: Introductionmentioning
confidence: 99%